Banking on the state : the political economy of public savings banks - Cassell, Mark K., 1964- (Finance matters (Newcastle upon Tyne, England), 2021)
Germany's public savings banks - Sparkassen - are a remarkable and puzzling phenomena. No other advanced industrial country relies as heavily on such small, public financial institutions to fuel its economy and how is it that such small institutions can drive one of the biggest and most successful economies in the world? In theory, their diminutive size should hinder their ability to function in an environment where they compete with the capital and muscle of major international banks. Yet at the height of the financial crisis, when other banks drastically reduced lending, new loans made by Sparkassen increased as they continued to provide liquidity and lend to start-up firms. How have they managed to survive the economic turmoil and global pressures of the last few decades? What has enabled them to stay at the heart of the German economy? In a period of neoliberal "too-big-to-fail" thinking, how have these relics of an ordoliberal past managed to flourish? Mark Cassell answers these and many other questions in his exploration of the unique entity that is Germany's public savings bank system and the lessons it offers to banking systems worldwide